Discord's apple - Vaughn, Carrie (New York : Tor, 2010)
Discovering a magical storeroom in a house she is destined to inherit, Evie Walker finds a cache of mythological and legendary artifacts that she is charged to keep out of the hands of villains who threaten the world with apocalyptic violence.
"A Tom Doherty Associates book."
Keywords: Antiquities -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Fantasy fiction